Review of radiation oncology emergencies in Lagos University Teaching Hospital, Nigeria - Adegboyega, Bolanle; Sowunmi, Anthonia; Alabi, Adewumi; Ojifinni, Oludoyinmola Omobolade; Adenipekun, A (South African journal of oncology, 2019)
Background: Radiation oncology emergencies (ROEs) are common in metastatic or locally advanced cancer accounting for a large proportion of radiotherapy indications in poor resource settings. Aim: To review pattern, presentation and outcome of ROEs in Lagos University Teaching Hospital (LUTH) and compare with an earlier study in the northern part of the country for possible geographical variation. Setting: A retrospective review of ROE record from 2008 to 2016 in LUTH. Method: Demographic data, clinical presentation, treatment and outcomes were analysed using charts and frequency tables. Results: Total of 458 cases of oncologic emergencies were reviewed. The mean age was 52.3 years with a male-to-female ratio of 1:2.2. The majority (85%) of the patients presented in stage IV, 10% stage III and 5% stage II diseases. Spinal cord compression was the commonest presentation seen in 53.9% of cases, brain metastases in 22.1% of patients and tumour haemorrhage in 22.5% of patients. Time from the onset of symptoms to treatment was between 24 and 48 h in 16.4%, > 48 h to 1 week in 64.4% and above 1 week in 19.2%. There was a complete or significant response in signs and symptoms in 77%, no improvement in 11% and 1.1% had disease progression. Conclusion: This study showed a varied pattern of presentation in ROEs from what was obtained in northern Nigeria, with spinal cord compression being the commonest in south west Nigeria. Despite a delayed onset in treatment, radiation therapy is vital in oncology emergencies management. There is a need for accessible functional radiotherapy centres in Nigeria to combat the delays in commencing treatment.
openalex: W2961553842 mag: 2961553842
Keywords: openalex:import

Patient's perception on the quality of radiotherapy services in two teaching hospitals in Nigeria - Sowunmi, Anthonia; Fatiregun, Omolara; Alabi, Adewumi; Zaccheus, Ibitoye A; Kingsley, Irurhe A; Oyedeji, Shola (Nigerian journal of medicine : journal of the National Association of Resident Doctors of Nigeria, 2015)
OBJECTIVE: Patient satisfaction is an important and commonly used indicator for measuring the quality in health care. Patient satisfaction affects clinical outcomes, patient retention, and medical malpractice claims. It affects the 13 timely, efficient, and patient-centered delivery of quality health care13.A review of quality of services from the patient's perspective could be a method of assessing in order to improve servicesand achieve total quality management. This study was designed to assess patients' perception on the quality of Radiotherapy services in Lagos University Teaching Hospital (LUTH) Lagos and University College Hospital (UCH) Ibadan. METHODOLOGY: This study is a cross-sectional study. This research lasted for a period of two months and all patients receiving radiotherapy within is period were included in this study. A total of 246 questionnaires were completed (152 and 94 in LUTH and UCH respectively) and the data collection was by semi-structured questionnaire. Data obtained were collected and analyzed using SPSS statistics [Social Sciences Statistical Package] 17.0 version. RESULTS: The findings of this research indicated that 68.4% in LUTH and 53.2% in UCH of the patients experienced good care. It also revealed that there is good interaction between the staff and the patient. Most of the patients spent more than 3 hours before receiving treatment and also the reason for such delay were not explained to them. The rate of preferential treatment was noted to be high. CONCLUSION: This study will contribute positively towards achieving effective and qualitative radiotherapy services by creating awareness for the need to minimize patient waiting time as well as the need to explain the reason for such delays. The department should adopt better ways of appointment system so that treatment will be on first come first serve basis. This study will contribute positively towards achieving effective and qualitative radiotherapy services by creating awareness for the need to minimize patient waiting time as well as the need to explain the reason for such delays. The department should adopt better ways of appointment system so that treatment will be on first come first serve basis.
openalex: W2526423058 mag: 2526423058
Keywords: openalex:import